The Efforts of Binmas unit with counseling to prevent drug abuse in Surakarta Jurisdiction - zulkifly ramadhan zulkifly (Police Studies Review, 2022)
This research is motivated by increase the drug abuse cases in jurisdiction area in Polresta Surakarta. The role of the police as preemptive and prevention function need to be questioned because the number of drug abuse in the hasn’t decrease and drug cases are the hightest criminality cases in Surakarta. This research was conducted which aims to know to how the implementation of education of Binmas Unit in Polresta Surakarta in order to prevent drug abuse in jurisdiction area of Polresta Surakarta. In this research, the author uses management theory to uses management theory to describe the implementation of counseling of Binmas Unit in rder to Prevent drug abuse in Surakarta. By using management elements, the authors hope to find out how the problems that exist in the efforts of the Binmas unit through counseling to prevent drug abuse in Surakarta Based on the results of this research, that the Binmas unit has not carried out outreach activities to prevent drug abuse to the fullest, and the conselling efforts have not gone well, so its recommended that the implementation of the health protocol of the Binmas unit involve BNN Surakarta and utilize media in providing counseling on drug abuse.